PROGRAM PELATIHAN PENGEMBANGAN KOMPETENSI GURU SEKOLAH INKLUSI DI SDN KARAWACI 3 TANGERANG - Yunita, Intan; Jessica, Madeline; Utami, Sylvia Dwi; handayani, penny (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2023)
SDN 3 Karawaci Tangerang is one of the schools designated as an inclusive school. Based on the results of theneeds analysis conducted using observation, study of school documents, interviews, and FGDs with teachers,principals, education personnel, students, and parents, it was found that one of the main challenges at SDNKarawaci 3 is the unpreparedness in accommodating the needs of students with disabilities in inclusive schools. Thismain problem is caused by dif iculties in identifying students with disabilities in the classroom, teachers' lack ofcompetence in teaching students with disabilities, inadequate facilities to accommodate students with disabilities,inef ective communication within the school ecosystem and a lack of discipline consistently applied by the school..The training program provided aims to improve teachers' competence in teaching in inclusive schools, with thetheme